Education and development in the Karakorum: educational expansion and its impacts in Gilgit-Baltistan, Pakistan - Benz, Andreas (ERDKUNDE, 2013)
Despite countless political declarations of commitment and continued efforts to improve rural education in the Global South, little progress has been made in the last decades. Some parts of the Gilgit-Baltistan Region in northern Pakistan constitute a rare exception in this respect. The analysis of this instructive example of a successful educational expansion allows for identifying key facilitating factors which made possible here what was doomed to fail elsewhere. Starting from very low education levels only six decades ago, parts of the region today are among the educational front-runners of Pakistan. Various education sector initiatives of the government, non-government institutions, denominational networks and the private sector have improved access to education and created new educational opportunities. This educational expansion has not been a homogeneous and linear process but is characterized by variegated ruptures, inequalities and disparities along regional, denominational, socio-economic, inter- and intra-generational as well as gendered lines. Many households could largely benefit from the educational opportunities in form of off-farm income generation and professional employment, but a group of continuously poor and educationally marginalized is threatened to be left behind.